MEMAHAMI KONSEP FILSAFAT ILMU - Suhari Suhari (ADISAM PUBLISHER, 2023)
Philosophy is the mother of all sciences which is expected to be a guide for humans to search for the ultimate truth, in this way it is hoped that humans will be able to think more positively and critically and become wise people in facing all the problems of life. This journal tries to discuss about. Concept of philosophy of science, Characteristics of philosophical thinking, Objects of philosophical study, Meaning and benefits of studying philosophy of science, Basic differences between philosophy, science, art and other knowledge. The approach method used in studying this topic is a literature review in which the literature taken is adapted to the subject of discussion and analyzed in depth so that conclusions, findings can be drawn and can be studied as a source of information in the future.